An empirical study of construction and demolition waste generation and implication of recycling. (15th July 2019) - Islam, Rashidul; Nazifa, Tasnia Hassan; Yuniarto, Adhi; Shanawaz Uddin, A.S.M.; Salmiati, Salmiati; Shahid, Shamsuddin
Highlights: This study adopted a holistic approach in investigating C&D waste generation. The waste generation and composition data were compared with other countries. The economic value of recycling will assist in managing the reuse programs. The classified data of C&D waste is suggested an effective waste management plan. Abstract: Associated with the continuing increase of construction activities such as infrastructure projects, commercial buildings and housing programs, Bangladesh has been experiencing a rapid increase of construction and demolition (C&D) waste. Till now, the generation rate of C&D waste has not been well understood or not explicitly documented in Bangladesh. This study aims to provide an approach to estimate C&D waste generation using waste generation rates (WGR) through regression analysis. Furthermore, analyses the economic benefit of recycling C&D waste. The results revealed that WGR 63.74 kg/m 2 and 1615 kg/m 2 for construction and demolition activities respectively. Approximately, in financial year (FY) 2016, 1.28 million tons (0.149 construction and 1.139 demolition) waste were generated in Dhaka city, of which the three largest proportions were concrete (60%), brick/block (21%) and mortar (9%). After collection they were dumped in either landfills or unauthorized places. Therefore, it can be summarized as: waste is a resource in wrong place. The results of this study indicate that rapid urbanization of Dhaka city would likely experience the peak in the generation of C&D waste. This paper thus designates that C&D waste recycling is an entrepreneurial activity worth venturing into and an opportunity for extracting economic and environmental benefits from waste. The research findings also show that recycling of concrete and brick waste can add economic value of around 44.96 million USD. In addition, recycling of C&D waste leads to important reductions in CO2 emissions, energy use, natural resources and illegal landfills. Therefore, the findings of WGR and economic values provide valuable quantitative information for the future C&D waste management exercises of various stakeholders such as government, industry and academy.